Refusal of Radioiodine Ablation in a Patient with Inoperable Locally Advanced Metastatic Papillary Thyroid Carcinoma: A Case Report - Ahmed, Tanvir; Begum, Fatima; Ferdous, Jasmin; Islam, Urnas; Tushra, Khadijatul; Munira, Sirajum (Bangladesh Journal of Nuclear Medicine, 2024)
Radioiodine ablation therapy (RAIT) with 131iodine is indicated in patients with differentiated thyroid carcinoma (DTC), done after total or near total thyroidectomy. RAIT is administered in repeated small doses in cases of inoperable DTC, as radioiodine may cause local tissue inflammation and edema. So, in some cases where thyroid carcinoma involves important surrounding or distal vital structures like the trachea, vessels, and brain tissue, radioiodine ablation is refused to avoid potential medical hazards. In this case report, a patient with inoperable, metastatic, locally advanced thyroid carcinoma has been discussed, as we had to refuse RAIT even after referral for ablation at National Institute of Nuclear Medicine & Allied Sciences (NINMAS). Bangladesh J. Nuclear Med. 26(2): 233-236, 2023